Kerjasama Pertahanan sebagai Bagian Diplomasi Pertahanan: Pertimbangan, Tujuan, Prinsip, dan Ruang Lingkup - Endro Tri Susdarwono (JATIJAJAR LAW REVIEW, 2022)
This study aims to provide an overview of defense cooperation as part of defense diplomacy in order to improve a country's military capability by looking at the considerations, objectives, principles, and scope. The type of research used is explanative research, while the type of data used in this study is secondary data. The data collection technique used in this research is library research by finding and collecting secondary data through scientific books related to the subject matter discussed. In addition, articles from the internet were collected to support the data in completing this research. The data analysis technique used was a qualitative content analysis data analysis technique, namely the author analyzed secondary data, then used theory to explain a phenomenon or event that the author studied. Defense cooperation is an international transaction carried out by two or more countries for a specific purpose, namely the "national interest" of cooperating countries, using a treaty or in writing and formally. This cooperation is very sensitive and will involve state sovereignty, security, stability, and people's welfare.